Autism as a Disorder of Biological and Behavioral Rhythms: Toward New Therapeutic Perspectives - Tordjman, Sylvie; Davlantis, Katherine S.; Georgieff, Nicolas; Geoffray, Marie-Maude; Speranza, Mario; Anderson, George M.; Xavier, Jean; Botbol, Michel; Oriol, Cécile; Bellissant, Eric; Vernay-Leconte, Julie; Fougerou, Claire; et al. (Frontiers in Pediatrics, 2015)
There is a growing interest in the role of biological and behavioral rhythms in typical and atypical development. Recent studies in cognitive and developmental psychology have highlighted the importance of rhythmicity and synchrony of motor, emotional and relational rhythms in early development of social communication. The synchronization of rhythms allows tuning and adaptation to the external environment. The role of melatonin in the ontogenetic establishment of circadian rhythms and the synchronization of peripheral oscillators suggests that this hormone might be also involved in the synchrony of motor, emotional and relational rhythms. Autism provides a challenging model of physiological and behavioral rhythm disturbances and their possible effects on the development of social communication impairments and repetitive behaviors or interests. This article situates autism as a disorder of biological and behavioral rhythms and reviews the recent literature on the role of rhythmicity and synchrony of rhythms in child development. Finally, the hypothesis is developed that an integrated approach focusing on biological, motor, emotional and relational rhythms may open interesting therapeutic perspectives for children with autism. More specifically, promising avenues are discussed for potential therapeutic benefits in autism spectrum disorder of melatonin combined with developmental behavioral interventions that emphasize synchrony such as the Early Start Denver Model (ESDM).